2015
DOI: 10.3390/ani5020362
|View full text |Cite
|
Sign up to set email alerts
|

The First Shared Online Curriculum Resources for Veterinary Undergraduate Learning and Teaching in Animal Welfare and Ethics in Australia and New Zealand

Abstract: Simple SummaryThere is a need for teaching Animal Welfare and Ethics in veterinary schools and we are developing online resources to meet this need. In this paper we describe how we prioritized the development of these resources by polling experts in the field.AbstractThe need for undergraduate teaching of Animal Welfare and Ethics (AWE) in Australian and New Zealand veterinary courses reflects increasing community concerns and expectations about AWE; global pressures regarding food security and sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Animal welfare and ethics scholars from eight Australasian veterinary schools developed the One Welfare Portal ( ), a shared online curriculum resource incorporating a range of interactive features, including case-based scenarios with guided ethical discussion [ 16 ]. The resource includes eight subsections, agreed upon by animal welfare and ethics educators on animal welfare science, ethics, companion animals, production animals, wild animals, animals used in research and teaching, animal use within sport, recreation and display and aquatic animals [ 13 , 14 , 15 , 16 ]. It incorporates a virtual online debating platform to facilitate student discussion of potentially polarising topics [ 17 ].…”
Section: Ethics In Veterinary Educationmentioning
confidence: 99%
“…Animal welfare and ethics scholars from eight Australasian veterinary schools developed the One Welfare Portal ( ), a shared online curriculum resource incorporating a range of interactive features, including case-based scenarios with guided ethical discussion [ 16 ]. The resource includes eight subsections, agreed upon by animal welfare and ethics educators on animal welfare science, ethics, companion animals, production animals, wild animals, animals used in research and teaching, animal use within sport, recreation and display and aquatic animals [ 13 , 14 , 15 , 16 ]. It incorporates a virtual online debating platform to facilitate student discussion of potentially polarising topics [ 17 ].…”
Section: Ethics In Veterinary Educationmentioning
confidence: 99%
“…These topics reflect the risk of Day One graduates being presented with dilemmas and scenarios that demand complex scientific, ethical, and communication skills. Plainly, ethical dilemmas are common in veterinary practice (27). A recent UK study revealed that the training of veterinary students in ethical decisionmaking was inadequate and that the shortfall in this aspect of veterinary education contributed to workplace stress (28).…”
Section: General Practicementioning
confidence: 99%
“…It is evident that if animals are still farmed intensively (the dominant dietary pattern), there will never be prosperity for these creatures, nor for the survival of the Earth's ecosystem. We think that the educational work that teachers could carry out with elementary school children, and, later, with students at higher education levels, including in universities (Andrzejewski, 2007;Johnson, 2015), might be a possible, albeit partial, "solution" to control an economic process that has always aimed exclusively at profit, and that has polluted and continues to pollute our planet. Educating new generations to respecting animals is certainly only a small, though essential part of this goal, since today's children will be tomorrow's adults and, therefore, must be prepared to handle climate issues that may already be irreversible.…”
Section: -Understand That the Destruction Of The Earth Also Means Thmentioning
confidence: 99%
“…This educational process should start already at elementary school level, in order to engender a significant imprint in very young students. The educational process may then continue throughout the years of secondary education and, perhaps, college too, with the support of a few targeted courses (Andrzejewski, 2007;Johnson, 2015). In this article, we propose to concentrate solely on primary education.…”
Section: Introductionmentioning
confidence: 99%